Service Innovation and Firm Performance of SMEs auto service: the mediating role of Pricing Capability - KanKam-Kwarteng, Collins; Gatsi, John Gartchie; Donkor, Jacob; Acheampong, Stephen (Archives of Business Research, 2018)
The purpose of this paper is to examine service innovation, pricing capability and firm performance of SMEs auto services, with service innovation (Independent Variables), pricing capability (mediating variable) and firm performance (Dependent Variable). Quantitative research principles were adopted where each of the path between the three variables were measured with co-efficient value (β) after controlling firm age, firm size and firm form. A total number of 200 service operators participated using convenience sampling technique The results showed that firm performance is influenced by both service innovation and pricing capability and that pricing capability mediates the relationship. The authors highlight the convenience nature of gathering data and the fact that the study was conducted in in a single city. This study contributes to the existing and growing literature on pricing capability and how it can moderate the relationship between service innovation and firm performance. The study opens up a research in an interesting area of the SMEs auto services industry in the context of a developing country.